THE ROLE OF ENDOCRINE FACTORS AND HEAT SHOCK PROTEINS (HSP60 AND GROEL) IN PREDICTING THE EFFECTIVENESS OF TREATMENT OF CLIMACTERIC SYNDROME - Sokol, I.V.; Berestoviy, V.O.; Martych, A.M.; Martynova, L.I.; Gromova, O.L.; Govsieiev, D.O. (World of Medicine and Biology, 2022)
The research was carried out during the examination and treatment of 158 patients with the climacteric syndrome. The patients were divided into two groups: 1 group included 80 patients receiving menopausal hormone therapy; group 2 included 78 women who were not treated. All patients from two groups had their levels determined: anti-Müllerian hormone, follicle-stimulating hormone, luteinising hormone, and thyroid-stimulating hormone. In addition, a study of the level of antibodies (IgG) to human heat shock protein 60 (HSP60) and its bacterial homolog (GroEl) was conducted. As a result of the multivariate analysis, a reduction (p=0.012) of the risk of not achieving the effect of treatment due to symptoms of estrogen-deficiency state was found for treated patients, OR=0.29 (95 % CI 0.11–0.76) in comparison with the untreated group female patients (when standardised by the level of anti-Müllerian hormone). A higher (p=0.017) risk of not achieving the effect of treatment due to symptoms of an estrogen-deficient state revealed at a higher level of anti-Müllerian hormone, OR=6.1 (95 % CI 1.4–27) for every 1 ng/ml. Indicators of HSP60 and GroEl do not affect the effectiveness of treatment of clinical manifestations of estrogen deficiency.
Keywords: perimenopause; climacteric syndrome; menopausal hormone therapy; HSP60